Early warning of precessing neutron-star black hole binary mergers with the near-future gravitational-wave detectors. Issue 3 (17th March 2022) - Tsutsui, T; Nishizawa, A; Morisaki, S
ABSTRACT: Since gravitational and electromagnetic waves from a compact binary coalescence carry independent information about the source, the joint observation is important for understanding the physical mechanisms of the emissions. Rapid detection and source localization of a gravitational wave signal are crucial for the joint observation to be successful. For a signal with a high signal-to-noise ratio, it is even possible to detect it before the merger, which is called early warning. In this article, we estimate the performances of the early warning for neutron-star black hole binaries, considering the precession effect of a binary orbit, with the near-future detectors such as A+, AdV+, KAGRA+ , and Voyager. We find that a gravitational wave source can be localized in $100 \, \rm {deg^2}$ on the sky before ∼10–$40 \, \rm {s}$ of time to merger once per year.